Classroom Assessment Literacy at Elementary Level: A Focused Group Discussion - Khalid, Hassan Arslan; Gull, Fariha (JCTE, 2024)
Classroom assessment literacy focuses on knowledge and practices of classroom assessment to maximize the students’ achievement. The focus of the present study was to investigate classroom assessment literacy and its practices among elementary school teachers. Elementary school teachers of district Hafizabad were investigated through focused group discussion. 15 elementary school teachers were selected through purposive sampling by considering their demographics. A semi-structured interview was conducted through selected participants which revealed the classroom assessment literacy and its practices among elementary school teachers. Interview protocol was developed based on seven standards of classroom assessment inventory developed by Mertler, 2003. The data were analyzed through narrative analysis. The study revealed that elementary school teachers know very little about classroom assessment. The classroom assessment literacy can be enhanced by providing continuous professional development in-service courses, mentoring by higher authorities and by giving freedom of assessment to teachers.